Correction: Kirste et al. Structural Analysis of Low Defect Ammonothermally Grown GaN Wafers by Borrmann Effect X-ray Topography. Materials 2021, 14, 5472 - Materials Editorial Office (MDPI AG, 2021)
The Materials Editorial Office would like to make the following change to this paper [...]